2022
DOI: 10.2196/28502
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Virtual Reality Interventions to Improve Psychosocial Functioning in Psychosis: Systematic Review

Abstract: Background Functional recovery in psychosis remains a challenge despite current evidence-based treatment approaches. To address this problem, innovative interventions using virtual reality (VR) have recently been developed. VR technologies have enabled the development of realistic environments in which individuals with psychosis can receive psychosocial treatment interventions in more ecological settings than traditional clinics. These interventions may therefore increase the transfer of learned ps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 71 publications
2
12
0
Order By: Relevance
“…Wang and colleagues found that 10 days of VRT improved participants’ working memory and executive function [ 26 ]. In addition, a systematic review also showed that VR-based interventions may represent a novel and efficacious approach for improving cognitive and psychosocial functioning [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and colleagues found that 10 days of VRT improved participants’ working memory and executive function [ 26 ]. In addition, a systematic review also showed that VR-based interventions may represent a novel and efficacious approach for improving cognitive and psychosocial functioning [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In direct practice, digital media are increasingly being used and conceptually framed. The potential of social work interventions based on VR applications has been spelt out (Trahan et al, 2019) and made available, especially for interventions on mental health and substance abuse issues (see, for example, Bordnick et al, 2012;Meyerbroker and Morina, 2021;Schroeder et al, 2022). In the same way, VR could be used in social work research and, specifically, also in qualitative research in social work.…”
Section: Concluding Reflections On the Potential Of Vr For Qualitativ...mentioning
confidence: 99%
“…Finally, psychosocial interventions and recovery-oriented rehabilitative interventions (e.g., cognitive remediation and metacognitive reflection and insight therapy (MERIT) etc.) have been rapidly developed in order to target cognitive and/or metacognitive deficits that can hamper the functional recovery of schizophrenic patients and in subjects at ultra-high risk of psychosis [ 203 , 207 , 208 , 209 , 210 ], even though they do not seem to be adequately integrated in the mental health services [ 24 , 203 ]. Similarly, family-based interventions and supported employment programs are seldom implemented in routine clinical practice [ 24 , 203 , 211 ].…”
Section: Schizophrenia Treatment and Interventionsmentioning
confidence: 99%